Analisis Kebutuhan Pengembangan Model Pendidikan Karakter Empati Anak Usia 5–6 Tahun Berbasis Teori Hoffman Melalui Picture Story Card - Meli Nurkharisma; Purwati Purwati; Fauziah Syarifatul Huriyah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Empathy is a fundamental socio-emotional competence in early childhood; however, empathy learning in preschool settings is generally implemented incidentally rather than through a systematic instructional model. This study aimed to analyze the needs for developing an empathy character education model for children aged 5–6 years based on Hoffman's Theory using Picture Story Cards as the foundation for the subsequent design phase. The study employed Educational Design Research (EDR) at the analysis and exploration stage. Data were collected through classroom observations, semi-structured interviews, and document analysis at TK Islam Al Azhar 33 Tasikmalaya and were analyzed qualitatively using the Miles, Huberman, and Saldana interactive model. The findings identified three major needs: (1) children demonstrated varying levels of empathy, particularly in recognizing emotions, expressing concern, and regulating social behavior; (2) teachers' efforts to foster empathy remained reactive and situational rather than systematically integrated into instructional practice; and (3) no instructional model or learning media specifically addressed empathy development based on Hoffman's developmental stages. The novelty of this study lies in establishing the conceptual foundation for integrating Hoffman's empathy development framework with Picture Story Cards into an early childhood character education model, an approach that has received limited attention in previous studies. Theoretically, the findings extend the application of Hoffman's Theory to instructional design in early childhood education. Practically, they provide evidence-based guidance for developing a structured, contextually relevant, and developmentally appropriate empathy learning model for preschool teachers